DAMPAK PERCERAIAN TERHADAP TUMBUH KEMBANG ANAK DI KABUPATEN GORONTALO - Syamsul Syamsul; Bala Bakri; Salma P. Tamu (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
Quality generations are born of quality families, harmonious home life, and are supported by a conducive environment. This is where the important role of the family in forming a quality generation with concern for child growth in all aspects, including physical, intellectual, emotional, moral, personality and spiritual development. The need for psychological attachment, the need for physical and mental stimulation requires enormous attention from their parents, and the need for security is a basic need that must be met for children in order to achieve optimal growth and development. The informants in this study were divorced parents. In this study using additional informants to support and complete the data obtained from the subject and informants. The data analysis used in this research is qualitative descriptive analysis which consists of data collection, data reduction, data display, and Conclusion Drawing / Verification. This research will be conducted in Gorontalo Regency with the locus of the Family Planning Village of Motinelo Village, Tabongo District, Gorontalo Regency. The results of the study identified several factors that were the source of divorce problems, namely the influence of internet / social media, early marriage / young marriage, liquor and domestic violence, behavior / lifestyle, and economic factors. The impact of divorce on child development is physical, social and psychological.